Is augmented reality going to bridge the gap between online and physical stores? - Nunes, Francisco de Almeida Gaspar Freixo (2021)
The first appearance of Augmented Reality (AR), a technology that mixes the real and virtual world through a device, goes back to 1968. An increasingly impact of digitalization in our society lead to the change of many business models and it has had an impact on retail. Retailers are now experimenting new ways to meet customer needs and expectations to remain competitive in the digital environment. Market pressure lead companies to invest more in technologies such as AR to improve their websites and platforms and work as a differentiation. This thesis seeks to investigate the impact of AR, through different devices, in bridging the gap between online and physical stores, since consumers are not able to experiment a product before buying it online. Through an online survey, it was possible to affirm that AR is a successful strategy to increment online performances even though the willingness to buy strictly online and purchase intention weren't directly affected by AR. Only a product's perceived informativeness increase due to the technology usage. Also, in fashion shopping the smart mirror had the best user acceptance and in furniture shopping the smartphone app took the lead. Thus, AR is able to bridge the gap between online and physical stores, according to the study, and the collected data might help companies to reevaluate their next steps, especially in the fashion and furniture industry, to remain competitive in the digital world.